Logicpower5: Smart Fan Chip / Muhammad Farhan Abd Halim [et al.] - Abd Halim, Muhammad Farhan; Mohd Najib, Muhammad Adib; Razali, Mohamad Hafiz; Ma'rof, Muhammad Syahir; Twet@Thwaites, Canigjia Song (2018)
Our smart chip is for control the speed of every fan connected with the microchip. It is very convenience for every fan in the world. The microchip is very rare because it is made from a combination of electronics component that is very flexible to handle.